2022
DOI: 10.3390/jmse10070877
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Three-Dimensional Interpolation Method in Hydrologic Analysis in the East China Sea

Abstract: The water mass in the East China Sea (ECS) shelf has a complicated three-dimensional (3D) hydrologic structure. However, previous studies mostly concentrated on the sea surface based on the sparse in situ and incomplete satellite-derived observations. Therefore, the 3D interpolation technology was introduced for the reconstruction of hydrologic structure in the ECS shelf using in situ temperature and salinity observations in the summer and autumn of 2010 to 2011. Considering the high accuracy and good fitness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The functions of RBF interpolation methods include Gaussian functions, multi-quadratic functions, inverse quadratic functions, and thin-plate splines. Among these, the RBF interpolation method combining cubic and thin-plate spline functions has proven to be an effective approach for reconstructing ECS shelf temperature and salinity with minimal errors [29]. Therefore, we chose the thin-plate spline RBF interpolation method for subsequent experiments.…”
Section: Interpolation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The functions of RBF interpolation methods include Gaussian functions, multi-quadratic functions, inverse quadratic functions, and thin-plate splines. Among these, the RBF interpolation method combining cubic and thin-plate spline functions has proven to be an effective approach for reconstructing ECS shelf temperature and salinity with minimal errors [29]. Therefore, we chose the thin-plate spline RBF interpolation method for subsequent experiments.…”
Section: Interpolation Methodsmentioning
confidence: 99%
“…Spatial interpolation methods, widely employed in atmospheric studies and other fields, offer a solution by mitigating the impact of insufficient ground-based observation data on accurately characterizing the spatial and temporal distribution characteristics of PM 2.5. These methods include spatiotemporal statistical models based on Kriging interpolation, spatial and temporal regression models based on Kriging interpolation integrated with remote-sensing AOD data, neural network models based on RBF interpolation, and 3D RBF interpolation for hydrological structure analysis [22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a comparative analysis involving 1982 cases and 29 different interpolation methods, Franke concluded that multiple quadratic RBF interpolation outperforms most other interpolation techniques. Today, RBF interpolation is employed extensively in contemporary geography, such as in the investigation of toxic substance distribution near mining areas, analysis of spatial distribution patterns of pollutants, and precipitation allocation within polluted sites (Ding et al, 2018;Qiao et al, 2019;Yang and Xing, 2021;Gao et al, 2022). The RBF interpolation method was chosen for this study due to several key advantages, such as efficient solutions to linear equations, easy extension into three dimensions, ability to offer smooth interpolation of scattered data, and adept handling of discrete spatial and temporal data (Carr et al, 2001;Fasshauer, 2007;Macêdo et al, 2009;Skala, 2010;Cuomo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Under such circumstances, introducing deep learning methods brings new possibilities for 3D interpolation. The application of three-dimensional interpolation technology is also used in medical imaging [9][10][11][12][13][14], hydrological analysis [15], atmospheric sciences [16], hydrodynamics [17], virtual reality [18], and other fields. Mikhailiuk A et al [19] first achieved the restoration of the full picture of seismic data from 20% of actual data through a deep autoencoder.…”
Section: Introductionmentioning
confidence: 99%